Reinterpretasi Tradisi Salim sebagai Sarana Internalisasi Nilai Karakter pada Anak Usia Dini - Shafa Alistiana Irbathy; Febriyani; Yuliana Nurshanti (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Today's progressive modernization has brought a lot of change in the lives of people. However, the change that happens tends to end in a moral crisis. Especially educational institutions must be expected to be able to educate people with a soul, morality and good character. One of them through character formation that can be done by parents and teachers with this research, will be studied further in relation to the interaction of "smoking and kissing" children to parents. The aim of this research is to find out the interaction of "shrimp and kissing" children to parents in the formation of character children in Tk Pkk Watugajah, Gunung Kidul, D.I. Yogyakarta as well as the obstacles faced by parents and teachers. This research uses a qualitative approach with a descriptive qualitatively type. Related to the character formed by the interaction of "shrinking and kissing" from the child to the parent. The qualitative research plan serves to create a comprehensive narrative picture of the child's character formation at PKK Watugajah, Gunung Kidul, D.I. Yogyakarta which is described through the interaction of "shim and kissing hands" from child to parent. The results of the research show that the child at PKK Watchogajah, Mount Kidul and D. I. Yogyakarta have applied the practice of "Shim and Kissing Hands" with various strategies that have been carried out by parents and teachers. Despite the many obstacles that parents and teachers face in shaping children's character through interactions such as kissing and kissing, understanding relevant theories and applying appropriate solutions can help overcome those obstacles. Thus, parents can be more effective in instilling moral and ethical values that are important for the development of children's character.